PENGEMBANGAN MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS INFORMATION AND COMMUNICATION TECHNOLOGY - Ramli, M.; Mulia Sari, Desi (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2023)
Nowadays, the development and progress of the times always have implications for thedevelopment of technology and information tailored to the needs and demands of society. IncludingIslamic religious education must provide for the mastery of science and technology in students, inaddition to fostering and developing religious sciences in themselves, so that Islamic religiouseducation is able to prepare and foster human resources as a whole who master science andtechnology and have faith and are able to practice religion well. This research uses library research,which is research that uses books, articles, the internet, and other online sources as data sources.The research is carried out by studying sources that are in accordance with the problems discussedby using content analysis to make it easier for the writer to filter the main ideas from variousexisting sources. ICT-based Islamic religious education learning media can be done anywhere andanytime. this supports the effectiveness and affection in learning Islamic religious education andstudents can develop according to their age. ICT-based learning media is media that is developedusing devices either hardware or software. The utilisation of this ICT-based Islamic religioseducation learning media is a very good issue for the continuity of education and can help inimproving the quality of education in Indonesia. ICT-based learning also affects the continuity oflearning which automatically affects the results. In addition, the use of ICT-based Islamic religiouslearning media is used so that students can apply various existing media in accordance withchanging times and become creative and innovative learning media as a source of Islamic religiouslearning and develop students' interest in learning